A study of plasma proteins (serum total protein, serum albumin), and thyroid function in children with protein-energy malnutrition - Chatterjee, Rachita; Sethi, Anuj S.; Verma, Manisha; Verma, Rajeev; Sethi, R. S.; Singh, Mayank (International Journal of Contemporary Pediatrics, 2023)
Background: The study's objective was to evaluate and compare total serum protein, serum albumin, and thyroid hormones in children with PEM (protein-energy malnutrition) and healthy controls. Methods: In this cross-sectional study, 100 children with PEM served as cases, while an equal number of age and gender-matched healthy children served as controls. 4 ml of venous blood were taken (3 ml in a plain vial and 1 ml in an EDTA vial) and immediately submitted for further investigation. SPSS software (version 25) was used to analyze the data. A p value of ≤0.05 was considered statistically significant. Results: PEM children have lower serum total protein, albumin level, total T3 (TT3), and total T4 (TT4) levels compared to healthy controls (p<0.0001). Mean TSH levels in cases and controls were nearly similar. There was no significant difference between serum TSH concentrations in PEM children and the controls. Grade I PEM had the highest mean total protein, serum albumin, T3, and T4 levels, followed by grades II, III, and IV. When mean total protein, serum albumin, T3, and T4 levels of each grade of PEM were compared to controls, mean total protein, serum albumin, T3, and T4 levels were substantially lower in each grade of PEM (p<0.0001). Conclusions: PEM children have low serum total protein and albumin levels. This is probably due to decreased oral intake of proteins and reduced biosynthesis. Serum TT3 and TT4 levels are lower in children with PEM than in healthy controls, which is most likely due to reduction in circulating plasma proteins.